New proposal for the physical fitness evaluation in football referees - Albaladejo Garcia, C.; Cejuela Anta, R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The aim of this study was the application of two batteries of tests in non-professional soccer referees, trying to determine which of them could be more specific for referees. The participants (n=10) were evaluated in three moments of the season (T1, T2, T3), performing the current battery used by the Football Federation of the Valencian Community (FFCV) (RSA: 6x40m/90"; Endurance: 2000m run) and another new proposal battery (RSA: 7x30m/25"; Endurance: Interval Test for Specific Endurance in Football, TIVRE-F). The results showed that the MAV of the referees significantly increased in the TIVRE-F between T1 and T3. The 7x30/25” test reported higher sprint decrement than 6x40/90” in T2 and T3. From this study we have obtained new data about the current FFCV tests, and we can conclude that the new battery of tests could adjust in a better way to the evaluation necessities.